Product Development Strategy for Increasing Competitive Advantage at BMT Al-Huda Grabag - Arum Maesaroh Putri; Yeny Fitriyani; Fuad Yanuar AR; Purwanto (Mutanaqishah: Journal of Islamic Banking, 2024)
The research aims to determine BMT Al-Huda Grabag's product development strategy. This research focuses on identifying internal and external elements and creating the right business strategy. Product development strategies are crucial to improving BMT's position and competitiveness. Internal factor identification results indicate that companies today have strengths such as satisfactory and quality services, structured financial services, e-commerce platforms that support UMKM, and cooperation with various parties. Internal factors that need to be more robust are limited human resources and incomplete information on digital platforms. Identification of external factors such as public ignorance of religion, inaccurate customer financial reports, and competition with renters and online loans are threats. This research will enhance understanding of product development and targeted strategies for improving the competitiveness of BMT using qualitative approaches and SWOT analysis. Furthermore, the research results are expected to provide new knowledge for similar research.